Adult acne: prevalence and portrayal in primary healthcare patients, in the greater Porto area, Portugal - Semedo, Diogo (2016)
Introduction: Though typically found in adolescents, acne frequently affects the adult population. In Portugal, no representative studies about acne prevalence in greater populational areas are known. This study had the following objectives: calculate acne prevalence in primary healthcare patients; its characteristics, including risk factors for onset and worsening; collect information concerning self-medication and/or prescribed treatment. Material and Methods: Application of a questionnaire and physical examination into a convenience sample, composed by adults from 20-60 years old that visited, in random days, five primary healthcare centers of the Greater Porto area. Results: From the 1,055 evaluated adults, acne prevalence was estimated at 61.5%. Only 36.8% of acne suffering adults was aware of their condition. More than half of tobacco users (62.3%) had acne. Just 25% of acne sufferers sought treatment. The most affected areas were the malars, differing from the younger disease form. Discussion: Acne prevalence was relatively higher than other studies. The results of this study have confirmed that acne seems to be related with increased calorie intake, tobacco smoking, whole milk and fat-reduced milk consumption, hirsutism, alopecia and seborrhea. Conclusion: In the primary healthcare set, more than half of adults were acne sufferers. These numbers show how important primary healthcare services can be in preventing and intervening when managing acne-related risk factors and psychosocial consequences.